Rethinking evidence-based and evidence-informed practice: a call for evidence-informed decision making in social work education and child welfare practice. Issue 2 (17th February 2022) - Lwin, Kristen; Beltrano, Natalie
ABSTRACT: Child welfare workers are tasked with addressing families' complex needs while navigating community systems, organizational policies and legislation. While Evidence-based and Evidence-informed Practice (EBP; EIP) are woven throughout child welfare systems and discussed in social work education, they are rarely applied to everyday service. This paper is a reconceptualization of EBP/EIP into Evidence-informed Decision Making (EIDM); a framework proposed for everyday child welfare practice. EIDM promotes the examination of multiple factors and their integration into everyday decisions, case plans, and service through critical thinking. This paper is targeted towards educators facilitating the knowledge and skills required for promoting critical thinking and developing future child welfare workers' practice.